Placental expression of endothelial and inducible nitric oxide synthase and NO metabolism in gestational hypertension: a case–control study. (16th February 2016) - Vignini, Arianna; Cecati, Monia; Nanetti, Laura; Raffaelli, Francesca; Ciavattini, Andrea; Giannubilo, Stefano R.; Mazzanti, Laura; Saccucci, Franca; Emanuelli, Monica; Tranquilli, Andrea L.
Abstract: Objective : Hypertension is one of the most common medical disorders in pregnancy and a role of nitric oxide (NO) metabolism has been described. Thus, the present work aimed at determining placental gene expression of eNOS and iNOS, to measure NO and ONOO − levels in patients with gestational hypertension (GH). Methods : Fifteen patients with GH and 15 healthy pregnant controls were enrolled in the study. Placental tissue was taken immediately after delivery and was stored at −80 °C until analysis. A piece of frozen tissue was homogenized in the appropriate buffer. Total RNA was extracted and was reverse transcribed to obtain complementary DNA that was used for real-time PCR for iNOS and eNOS expression, whereas NO and ONOO − production were measured by commercially available kits. Results : Placental eNOS and iNOS mRNA levels were significantly reduced in GH when compared to controls. NO and ONOO − production were both significantly higher in GH than controls. Conclusions : The reduced eNOS and iNOS gene expression in women with GH reinforces the hypothesis that the mechanisms involving NO pathways, may promote oxidative damage, by contributing to the reduced blood flow and increased resistance in the feto–maternal circulation and suggests the use of NO modulators as useful tools in GH management.